здесь нужно выделить полный квадрат по
формуле: а²+2аb+b²=(a+b)²
x²+6x+y²-2y+10=(x²+6x+9)+(y²-2y+1)=
=(x+3)²+(y-1)²≥0
так как (x+3)²≥0 и (у-1)²≥0
аналогично
х²-4х+у²+2у+5=(х²-4х+4)+(у²+2у+1)=
=(х-2)²+(у+1)²≥0
так как (х-2)²≥0 и (у+1)²≥0
Відповідь:
Покрокове пояснення:
Сума невідємних виразів є невідємною
а²+b²>=0 для всіх а та b
здесь нужно выделить полный квадрат по
формуле: а²+2аb+b²=(a+b)²
x²+6x+y²-2y+10=(x²+6x+9)+(y²-2y+1)=
=(x+3)²+(y-1)²≥0
так как (x+3)²≥0 и (у-1)²≥0
аналогично
х²-4х+у²+2у+5=(х²-4х+4)+(у²+2у+1)=
=(х-2)²+(у+1)²≥0
так как (х-2)²≥0 и (у+1)²≥0
Відповідь:
Покрокове пояснення:
Сума невідємних виразів є невідємною
а²+b²>=0 для всіх а та b